Future advances in UK marine fisheries policy: Integrated nexus management, technological advance, and shifting public opinion. (January 2023) - Kemp, Paul S.; Subbiah, Gowshika; Barnes, Richard; Boerder, Kristina; O'Leary, Bethan C.; Stewart, Bryce D.; Williams, Chris
Abstract: Having left the European Union, the UK Fisheries Act (hereafter referred to as the Act) provides a framework that may advance sustainable marine resource management. This requires the bias towards social-economic concerns to be recognised, and greater emphasis to be placed on securing the natural capital to support fisheries. A Joint Fisheries Statement (JFS) to be published in 2022 by the UK's devolved fisheries authorities will set out how the objectives of the Act will be achieved. While recognising the value of principles of the Act, this article challenges the current management framework in light of the wider challenges in fisheries practice. It argues for more emphasis on ecological and fisheries regeneration, and maximising societal benefits rather than yields. Three recommendations are provided: (1) an integrated and more holistic Fisheries-Energy-Environment Nexus resource management approach would better utilise systems thinking to optimise trade-offs and synergies between competing domains to achieve fisheries, conservation and other environmental goals ( e.g. delivering the national net zero strategy); (2) the use of best available technologies as is reasonably practicable to monitor compliance and facilitate enforcement should be a regulatory requirement under the JFS; (3) the fisheries and marine conservation science community should work with other stakeholders to change the media narrative, public opinion, and political direction away from a "business-as-usual" model that risks long-term degradation of the marine fisheries resource.